Sergeia podlipaevi gen. nov., sp. nov. (Trypanosomatidae, Kinetoplastida), a parasite of biting midges (Ceratopogonidae, Diptera) - Svobodová, Milena; Zídková, Lenka; Čepička, Ivan; Oborník, Miroslav; Lukeš, Julius; Votýpka, Jan (International journal of systematic and evolutionary microbiology, 2007)
Three strains of a trypanosomatid protozoan were isolated from the midguts of two naturally infected species of biting midges [Culicoides (Oecacta) festivipennis and Culicoides (Oecacta) truncorum] and characterized by light and electron microscopy and by molecular techniques. Morphological characteristics and sequences of the 18S rRNA, 5S rRNA, spliced leader RNA and glycosomal glyceraldehyde-3-phosphate dehydrogenase genes indicate that the studied flagellates represent a novel phylogenetic lineage within the Trypanosomatidae. Based on phylogenetic analyses, the novel endosymbiont-free, monoxenous trypanosomatid was classified as Sergeia podlipaevi gen. nov., sp. nov. Interestingly, it is closely related to another trypanosomatid species that parasitizes the sand fly Lutzomyia evansi, a blood-sucking dipteran from South America. The type strain of S. podlipaevi sp. nov., ICUL/CZ/2000/CER3, was obtained from Malpighian tubes. Of 2518 females of seven species of biting midges trapped in the Czech Republic, more than 1.5 % were infected by trypanosomatid parasites. An unrelated insect species, Culicoides (Monoculicoides) nubeculosus, was experimentally infected with S. podlipaevi, demonstrating that its host range extends to different subgenera of biting midges.
Keywords: DNA, Kinetoplast; protozoální DNA; Sequence Homology, Nucleic Acid; fylogeneze; RNA, Ribosomal, 18S; RNA, Ribosomal, 5S; Sequence Analysis, DNA; Phylogeny; ribozomální DNA; sekvenční analýza DNA; molekulární sekvence - údaje; Gastrointestinal Tract; sekvenční homologie nukleových kyselin; DNA, Protozoan; RNA, Protozoan; elektronová mikroskopie; geny rRNA; Trypanosomatina; RNA ribozomální 5S; Animals; Genes, rRNA; glyceraldehyd-3-fosfátdehydrogenasa (fosforylační); zvířata; Microscopy, Electron; Ceratopogonidae; gastrointestinální trakt; RNA protozoální; Molecular Sequence Data; DNA, Ribosomal; RNA ribozomální 18S; kinetoplastová DNA; Glyceraldehyde-3-Phosphate Dehydrogenase (Phosphorylating)